Market Power, Growth, and Inclusion : The South African Experience - Thakoor, Vimal (Washington, D.C. : International Monetary Fund, 2020)
Before the pandemic, the South African economy remained stuck in low gear, with anemic growth, stagnant private investment, and a shrinking tradable sector. Subdued growth has raised unemployment, poverty, and inequality, hindering inclusion efforts. The pandemic has worsened economic and social vulnerabilities. Economic recovery and social inclusion hinge critically on structural reforms to boost competiveness and growth. Product markets represent a cornerstone of the reform strategy. Firms have used their market power to drive up prices and limit competition. Important state-owned monopolies provide low-quality services, while representing a fiscal drag. Existing regulations inhibit the entry of both domestic and foreign firms. Addressing product markets constraints could boost per capita growth by 1 percentage point-adding about 2 1\2 percentage points to headline growth-and foster greater inclusion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet